HUBUNGAN ANTARA SLEEP HYGIENE DENGAN GANGGUAN TIDUR PADA REMAJA DI SMKN 1 JAYAKERTA - Padila, Euis; Manalu, Lisbet Octavia (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Introduction: Sleep quality includes quantitative aspects of sleep, such as sleep duration, sleep latency as well as subjective aspects of sleep. A person who experiences sleep problems will affect their sleep quality. Sleep hygiene is a tendency that can affect sleep quality including sleep habits such as sleep schedule in a day, physical activity, alcohol use, nicotine and caffeine can affect sleep quality. Research Objectives: This study aims to determine the relationship between sleep hygiene and sleep disorders in adolescents. Research Methods: This study used a descriptive correlative design with a cross sectional approach. The adolescent population used was all 12th grade students of SMKN 1 Jayakerta as many as 118 people. The sampling technique used is random sampling is a technique that does not provide equal opportunities for each member of the population to become a sample. with a total sample size of 91 people. Data collection tools using questionnaires. Data analysis used is the rank spearment correlation test. Results: The results showed that the statistical test results obtained a value of p = 0.000 <0.05, it can be concluded that there is a very significant relationship between sleep hygiene and sleep disorders in adolescents at SMKN 1 Jayakerta. Conclusion: There is a relationship between sleep hygiene and sleep disorders in adolescents at SMKN 1 Jayakerta.